Achievement of teaching - learning activity in Lao language subject “editing alphabet and words” by using TAI technique for 3rd year students of Lao language and Literature program academic year 2020 - 2021 - CHANHTHAHONG , Khamxay; SYSOUPHANH, Sangkhom; LITTHAVONG, Somvang; VIENGKEOBOUKHAM, Somchay; INTHAVONG, Vienganousouk; PHATHOUMVANH, Phanthamanath; INVANKHAM, Maiphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research was intended to study the effectiveness of teaching and learning the Lao language by using the TAI technique to edit the alphabet and words of 3rd-year student in the program of Lao Language and Literature, Faculty of education, the academic year 2020 - 2021. The aims of this research were: 1) To compare the achievement in learning the Lao language after conducted teaching and learning by using the TAI technique to edit the alphabet and words for students in year 3; 2). To study the students’ satisfaction in conducting teaching and learning the Lao language by using TAI technique. The target group of this study were 3rd-year students of the Lao Language and Literature program, Faculty of education, Souphanouvong University, in the first semester of 2020 – 2021 with the total number of the research samples were 16 students (8 women). The research instrument consists of three components; 1) teaching plans, 2) achievement tests before and after using TAI technique, 3) a questionnaire of student satisfaction. The data were analyzed by using descriptive statistics in the SPSS program to find out the standard deviation and paired sample t-test. The result of this research found that: 1) the students’ achievement before and after using the TAI technique in teaching-learning activity were different with the significance of statistic value 0.00%, with descriptive statistic after using the TAI technique ( ) higher than before using TAI technique (), with 95% confidence level of hypothesis testing. 2) The students were most satisfied in the teaching-learning activities (,).The result shows that students were satisfied and the teaching-learning activities using the TAI technique were highly effective.